2011
DOI: 10.1101/lm.2016411
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual similarity promotes generalization of higher order fear learning

Abstract: We tested the hypothesis that conceptual similarity promotes generalization of conditioned fear. Using a sensory preconditioning procedure, three groups of subjects learned an association between two cues that were conceptually similar, unrelated, or mismatched. Next, one of the cues was paired with a shock. The other cue was then reintroduced to test for fear generalization, as measured by the skin conductance response. Results showed enhanced fear generalization that correlated with trait anxiety levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 47 publications
(59 reference statements)
7
52
1
Order By: Relevance
“…This is in line with previous findings on the expectancy and prediction of aversive events. In fear learning, category information, derived from pre-existing conceptual relationships or the construction of novel categories, has been shown to impact generalization of fear responses (Dunsmoor et al, 2012;Dunsmoor, White, & LaBar, 2011;Dymond et al, 2013). In the present study, we were able to show similar generalization of symptom expectancies using aversive CO 2 -induced respiratory symptoms as a UCS.…”
Section: Discussionsupporting
confidence: 70%
“…This is in line with previous findings on the expectancy and prediction of aversive events. In fear learning, category information, derived from pre-existing conceptual relationships or the construction of novel categories, has been shown to impact generalization of fear responses (Dunsmoor et al, 2012;Dunsmoor, White, & LaBar, 2011;Dymond et al, 2013). In the present study, we were able to show similar generalization of symptom expectancies using aversive CO 2 -induced respiratory symptoms as a UCS.…”
Section: Discussionsupporting
confidence: 70%
“…Dunsmoor, White et al (2011) showed that a conceptually related stimulus pair (e.g., pictures of a spider and a spider web)-as compared to a conceptually unrelated stimulus pair (e.g., a spider and a waste barrel)-promoted the transfer of conditioned SCRs after one stimulus was paired with shock. In this case, prior conceptual knowledge on the association between spiders and webs likely strengthened the interstimulus pre-association.…”
Section: Nonperceptual-based Fear Generalizationmentioning
confidence: 99%
“…Findings from a growing number of studies suggest that fear and anxiety often arise due to overgeneralization of threat cues along non-arbitrary (physical) continua, such as emotional, perceptual and intensity continua (Dunsmoor, Mitroff, & LaBar, 2009;Dunsmoor, White, & LaBar, 2011;Lissek et al, 2008Lissek et al, , 2010Vervliet, Kindt, Vansteenwegen, & Hermans, 2010). However, if it can be shown that both avoidance and expectancy ratings may be shown to generalize along a nonphysical, formal continuum, in the absence of any formal similarity or other direct associations between the stimuli, then such "symbolic generalization" may add a novel dimension to the understanding of generalized anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%